ByzRev 07.2025.063: Demetra Samara, Ethopoeia Dramatica by Manuel Philes: Introduction, Critical Edition, English Translation, Commentary: (Hellenica 112). Alessandria: Edizioni dell’Orso 2024. - Kubina, Krystina (The Byzantine Review, 2025)
Demetra Samara, Ethopoeia Dramatica by Manuel Philes: Introduction, Critical Edition, English Translation, Commentary (Hellenica 112). Alessandria: Edizioni dell’Orso 2024. x+230 pp. – ISBN 978-88-3613-522-6